(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Agriculture sector provides not only employment opportunities and food but also supply raw materials to a very large proportion of the major industries. In India agriculture sector contributed more than 14.7 percent of total export earnings. In fact during last decade the performance of agriculture sector in the Indian economy in contradictory year has not been quite satisfactory because of slowdown in growth, this sector has faced a number of challenges. Recent trends that have raised concern regarding food security farmer’s income and poverty are slowdown in growth. Economic disparities between irrigated and rain fed area. All these reasons call for change which attracts farmers to shift in the consumption pattern in favour of high value horticulture crops like fruits and vegetables from staple food crops such as rice wheat and coarse cereals.